Exhaust silencers with minimum power loss - SHENODA, F. B. (Archives of Acoustics, 1986)
Based on the principle of reflection free duct termination, silencers were designed. These silencers were applied to reduce the exhaust noise of internal combustion engines.Acoustical and mechanical measurements have been taken as a function of engine speed for both full and partial load. For comparison, the same measurements have also been carried out on a conventional dissipative silencer of equal length, and also, for purposes of reference, on the exhaust pipe without a silencer.A high level of acoustic absorption could be realized over a wide frequency range, without changing both the electric power and the fuel consumption of the applied engine, with respect to those for an untreated pipe.